READER-RESPONSE CRITICISM: THE ROLE OF THE AUTHOR, TEXT AND READER IN INTERPRETATION - Willis, Fitzroy (QUAERENS: Journal of Theology and Christianity Studies, 2025)
Reader-Response Criticism (RRC) examines how meaning is derived from texts, emphasizing the roles of the author, text, and reader in interpretation. Traditionally, RRC scholarship has focused on the interaction between text and reader, with minimal attention to the author’s role. This paper broadens the scope to include the author alongside the text and reader, offering a more comprehensive analysis of RRC in biblical interpretation. Using historical and contemporary RRC perspectives, this study categorizes interpretive approaches into conservative, moderate, and liberal, each with varying emphases on the author, text, and reader. The article analyzes key theories in conservative RRC, which prioritize the author’s intent, moderate RRC, which balances reader and text, and liberal RRC, which centers the reader’s interpretation. Findings reveal significant implications for understanding scriptural and literary texts, where the choice of RRC approach shapes interpretive outcomes and highlights potential conflicts between subjective and objective readings. This study contributes to the field by providing a structured framework for RRC, underscoring the complexity of meaning-making and advancing critical discourse on the interpretive process.